2013
DOI: 10.4236/fns.2013.43043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Instant Controlled Pressure Drop Process Coupled to Drying and Freezing on Antioxidant Activity of Green “Poblano” Pepper (<i>Capsicum annuum</i> L.)

Abstract: Different food operations have been intensified through assisting them by instant controlled pressure drop DIC treatment. Such processes should be defined in order to preserve the main nutritional and sensorial contents of the raw material. The present paper is dedicated to study the evolution of the main bioactive compounds (total phenolics and flavonoids) and functional properties such as the antioxidant activity of processed samples in the case of Green "Poblano" Pepper (Capsicum annuum L.). Results issued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(71 reference statements)
3
8
0
Order By: Relevance
“…Whereas, the retention percentage of the flavonoids compounds was 63.55% in the PD-dried seedless grapes versus to 47.38% in the ADdried seedless grapes. This observation is similar to that mentioned by Téllez-Pérez et al, (2013); Yi et al, (2016a) and Chiang et al, (2017).…”
Section: The Effect Of the Puff Drying Methods On The Antioxidant Compounds Of Seedless Grape As Compared With The Conventional Air Dryinsupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas, the retention percentage of the flavonoids compounds was 63.55% in the PD-dried seedless grapes versus to 47.38% in the ADdried seedless grapes. This observation is similar to that mentioned by Téllez-Pérez et al, (2013); Yi et al, (2016a) and Chiang et al, (2017).…”
Section: The Effect Of the Puff Drying Methods On The Antioxidant Compounds Of Seedless Grape As Compared With The Conventional Air Dryinsupporting
confidence: 92%
“…For example, it has been reported that the explosion-puffing significantly increased in the total polyphenol content of jujubes, which led to a corresponding increase in antioxidant properties (Du et al, 2013). These results are coincident with the data observed by Téllez-Pérez et al, (2013); Yi et al, (2016a) and Chiang et al, (2017). 4), it could be demonstrated that the dried seedless grapes by using PD method had the highest amount of total flavonoids (84.85 mg/100g DM) than those found in dried seedless grape by using AD method (63.26 mg/100g DM).…”
Section: The Effect Of the Puff Drying Methods On The Antioxidant Compounds Of Seedless Grape As Compared With The Conventional Air Dryinsupporting
confidence: 84%
See 1 more Smart Citation
“…Téllez-Pérez et al [34] evaluated the effects of drying and freezing couple to the DIC process on the phytochemical content and the antioxidant activity of Green Poblano Pepper (Capsicum annuum, L.). Traditional airflow drying (HAD), freeze drying (FD), and traditional freezing (TF) were studied as controls.…”
Section: Swell-drying In Increasing Functional Availability Of Activementioning
confidence: 99%
“…Results showed that the total phenol content (TPC) varied widely according to different drying and freezing conditions. Compared to raw material (RM), both DIC and frozen samples [34].…”
Section: Swell-drying In Increasing Functional Availability Of Activementioning
confidence: 99%